Current Possibilities for Detection of Loosening of Total Hip Replacements and How Intelligent Implants Could Improve Diagnostic Accuracy - Ruther, Cathérine; Timm, Ulrich; Ewald, Hartmut; Mittelmeier, Wolfram; Bader, Rainer; Schmelter, Rico; Lohrengel, Armin; Kluess, Daniel (IntechOpen, 2012)
None